Key factors influencing school violence in Peruvian emblematic schools post-pandemic - Hilda Beraun-Vasquez; Eugenia Fabian-Arias; Maribel Ruiz-Balvin (Frontiers in Education)
This study aims to determine the factors influencing school violence among students in emblematic educational institutions in the Junín region post-pandemic. A quantitative and explanatory study was conducted with a sample of 1,656 students, aged 12 to 18, selected through simple random sampling. Data collection instruments included a questionnaire for assessing various factors and the School Bullying and Violence Test (AVE) for measuring school violence. Validity was ensured through expert judgment and a pilot test, while reliability was assessed using Cronbach’s alpha, with values of 0.832 and 0.802. Structural equation modeling was used for analysis. The personal factor (β = 0.39, p < 0.001) had a direct and significant influence on school violence. The family factor showed a low and negative relationship (β = −0.06, p < 0.017). The educational factor also presented a negative relationship (β = −0.16, p < 0.001), indicating that changes in norms and structure could reduce violence. Adolescents’ personal factors, such as emotional distress, irritability, and anxiety, directly influence school violence. The family factor did not significantly influence violence, as families felt more cohesive during confinement, acting protectively post-pandemic. The educational factor impacts school violence when norms are not enforced, supervision is insufficient, and spaces are limited.